A DFT investigation of some (formally) redox isomerization reactions of bis(pentalenyl)iron and bis(azulenyl)iron. (28th January 2015) - Deramchi, Karima; Maouche, Boubekeur; Kahlal, Samia; Saillard, Jean-Yves
Graphical abstract: The intramolecular interconversion of the Fe(C8 H6 )2 and Fe(C10 H8 )2 isomers are symmetry-dependent and related to the nodal properties of the LUMO and HOMO of their C2v intermediate, respectively. Abstract: The isomerization reactions of Fe(C8 H6 )2 and Fe(C10 H8 )2 have been investigated by the means of DFT calculations. Several low-energy isomers having a C–C bond linking the two ligands exist in both cases, in addition to an isomer in which the two ligands are not connected. Calculation show that, apart one exception in the bis(azulenyl)iron case, all the isomerization reactions are formal intramolecular redox processes. These reactions are under symmetry control and related to the nodal properties of the non-coupled bis(pentalene) iron LUMO and bis(azulene)iron HOMO, respectively. Although most of the isomer interconversion are symmetry-forbidden, the intramolecular racemization of the experimentally characterized isomers of bis(pentalenyl)iron and bis(azulenyl)iron are allowed and should be observed.